2008
DOI: 10.1103/physrevlett.100.167206
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Correlated Electrons in the[Ni(hmp)(ROH)X]4Single Molecule Magnet: A<

Abstract: The single-molecule magnet [Ni(hmp)(MeOH)Cl]4 (hmp denotes the anion of 2-hydroxymethylpyridine and Me denotes methyl) is studied using both density functional theory (DFT) and the DFT+U method, and the results are compared. By incorporating a Hubbard-U like term for both the nickel and oxygen atoms, the experimentally determined ground state is successfully obtained, and the exchange coupling constants derived from the DFT+U calculation agree with experiment very well. The results show that the nickel 3d and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…Such effects would results from self-consistent changes in the electronic wavefunctions. This observation is consistent with that of Chao et al [17] who found that inclusion of Hubbard U corrections for both Ni 3d and O 2p state are important in similar systems. Radon finds that the S = 2 (quintet) state is higher in energy by 0.8 eV if full Slater exchange is used in the B3LYP functional but lower in energy by 0.8 eV when full exact exchange is used instead.…”
Section: The S = 2 Porphyrin Structures: Flat Vs Bentsupporting
confidence: 82%
“…Such effects would results from self-consistent changes in the electronic wavefunctions. This observation is consistent with that of Chao et al [17] who found that inclusion of Hubbard U corrections for both Ni 3d and O 2p state are important in similar systems. Radon finds that the S = 2 (quintet) state is higher in energy by 0.8 eV if full Slater exchange is used in the B3LYP functional but lower in energy by 0.8 eV when full exact exchange is used instead.…”
Section: The S = 2 Porphyrin Structures: Flat Vs Bentsupporting
confidence: 82%
“…al. [20] a Experimental data is taken from [28] b Experimental Data is taken from [29] c BSDFT calculation from ref [21] d BSDFT calculation from ref [16] Our calculated data agree with the experimental value to within 15%, for both molecule with and without Acetate Bridge, compare to 65% deviation given by broken symmetry Density Functional theory. …”
Section: Calculation Of J For Bimettalic Mn(iv) Complexes and Validatsupporting
confidence: 71%
“…al. [20] was used for the calculations. We applied Hubbard U parameter on Mn atom, as well on the ligand oxygen and nitrogen atoms, coordinating the Mn atom.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Also, there are numerous evidences of the importance of the Hubbard term for oxygen [19][20][21] and nitrogen 22 atoms; the U value for oxygen ranging from 1.5 eV 22 to 8.5 eV. 19 C. Cao et al 20 found that increasing U for oxygen above 6 eV slightly effects on the magnetic coupling constant in single-molecule magnet Ni(hmp)(MeOH)Cl 4 . The corresponding Hubbard scheme accounting for U for 2p-electrons of oxygen was named DFT+U p+d (or DFT+U d +U p ).…”
Section: -mentioning
confidence: 99%